Studies on fuzzy decision making in Turkish Universities: An overview - Kentli, Aykut (My University, 2011)
Fuzzy sets theory bridges the gap between boolean logic and human logic which is including a high degree of ambiguity. It has been used to accomplish different tasks (to control, to optimize, to make decision etc.) in different areas (education, management, medicine, technical, military etc.). Many fuzzy decision making methods have been proposed over the years. Classification of these methods and their applications can be found in literature. However, most of these studies concern only one method or one specific application area or one certain time interval. From this point of view, this study aims to show the studies on application of fuzzy decision making in Turkish universities. It is expected that this study will help the researchers on working fuzzy decision making as it is beneficial to know the previous studies on their topic, in an organized way and there is no similar study on this area. It mainly surveys the PhD and MSc Theses in Turkey on fuzzy decision making and the unclassified studies are not given to limit the study. Classified studies are summarized, compared and future recommendations are given for new researchers.
Keywords: Fuzzy Decision Making, Review Paper